Diary of a bad year - Coetzee, J. M. 1940- (Viking, 2008)
At the center of the book is Senor C, an aging author who has been asked to write his thoughts on the state of the world by his German publisher. These thoughts, called "Strong Opinions," address a wide range of subjects and include a scathing indictment of George W. Bush, Dick Chaney, and Tony Blair, as well as a witheringly honest examination of everything from Machiavelli and the current state of the university to music, literature, and intelligent design, offering unexpected perceptions and insightful arguments along the way.